KEMAMPUAN REPRESENTASI MATEMATIS DAN KEAKTIFAN BELAJAR SISWA SMP - Laila, Nur; Hidayat, Wahyu; Hendriana, Heris (IKIP Siliwangi, 2018)
This study aims to analyze and examine in depth about the ability of mathematical representation that influenced the active learning of junior high school students. The method in this research using correlational method with quantitative approach. The population in this study is all junior high school students in the city of Bandung with a sample of students selected class IX Junior High School in the city of Bandung amounted to 22 students. Instrument in this research is a test of Reverentasi mathematical ability as much as 6 item and student activity scale as much as 21 scale statement. The results of this study concluded that the ability of mathematical representation of junior high school students is positively influenced by learning activeness of 93%, while 7% is influenced by other factors outside of student learning activity.